2019
DOI: 10.1177/0361198119847617
|View full text |Cite
|
Sign up to set email alerts
|

Method to Identify and Visualize Barriers in a Low-Stress Bike Network

Abstract: Low-stress bike networks are often disconnected, with gaps or barriers that make travel between two points impossible without riding on high-stress roads. Barriers can also force long detours that people are not willing to make. Although existing methods of low-stress bike network analysis have been used to point out some barriers, a method was needed to systematically identify and draw barriers to assist in network planning. Such a method was developed, taking only the low-stress network as an input, and yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies ( 2 , 4 ) have shown how roads with high traffic stress, together with natural and manufactured barriers such as rivers and freeways, create barriers to cycling, sometimes dividing a city into islands with no connection to each other. However, studies of low-stress bike networks have paid little or no attention to the barrier effect of directional restrictions.…”
mentioning
confidence: 99%
“…Previous studies ( 2 , 4 ) have shown how roads with high traffic stress, together with natural and manufactured barriers such as rivers and freeways, create barriers to cycling, sometimes dividing a city into islands with no connection to each other. However, studies of low-stress bike networks have paid little or no attention to the barrier effect of directional restrictions.…”
mentioning
confidence: 99%